Effect of fertilizer and endomycorrhizal inoculum on growth and nutrient uptake of cocoa (Theobroma cacao L.) seedlings - Chulan, H. Azizah (Springer-Verlag, 1991)
A greenhouse experiment was carried out to evaluate the influence of vesicular-arbuscular mycorrhiza (VAM) on growth and nutrient uptake of cocoa seedlings treated with five levels of palm oil mill effluent, in an unsterilized Oxisol and an Ultisol, either with or without addition of the VAM fungus Scutellospora calospora (Nicol. & Gred.) Walker and Sanders. Inoculation with the VAM fungi significantly increased nutrient uptake and plant growth in both soils. The dry matter yield, and the tissue N and K concentration in the plant tops increased significantly with increasing levels of palm oil mill effluent applied to both the Oxisol and the Ultisol. The maximum tissue P concentration, however, was obtained from plants grown in the Ultisol that was given 50.0 g palm oil mill effluent per kg while the maximum P recovery of 26% was obtained from plants given only 16.7 g effluent per kg. Overall, the percentage of P recovery decreased with the addition of increasing levels of palm oil mill effluent. In the Oxisol, the tissue P concentration increased with the addition of increasing levels of palm oil mill effluent, but the maximum recovery of P was recorded from plants given only 0.3 g effluent per kg. The percentage P recovery decreased with subsequent additions of the effluent. © 1991 Springer-Verlag.